2021
DOI: 10.15408/insaniyat.v5i2.17356
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Motivation on Staff Performance and Job Satisfaction in The University of Ilorin Library

Abstract: This study examined the effects of motivation on job satisfaction and performance of librarians in University of Ilorin Library. It was observed that many employers have attempted several programs to motivate their employees, yet they have not worked for every category of staff in the library. Descriptive survey design was adopted for the study. The population of the study was made up of professional and paraprofessional librarians, which totaled 46 librarians. Relevant data for the study was collected using q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…A significant number of studies reported the emerging services in the field of librarianship (Anyaegbu and Wali, 2020; Auster and Chan, 2004) and these advancements in Information Technology were motivating library professionals to focus on professional development for offering innovative library services to the users (Chan and Auster, 2005; Issa, 2021). Different emerging technologies were influencing information professionals to attend PD activities for enhancing relevant skills for the provision of satisfactory services to their customers (Cobblah and van der Walt, 2017); adoption of constant evolving changes was indispensable in the present era according to changing market requirements (Cossham and Fields, 2006).…”
Section: Data Analysis and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A significant number of studies reported the emerging services in the field of librarianship (Anyaegbu and Wali, 2020; Auster and Chan, 2004) and these advancements in Information Technology were motivating library professionals to focus on professional development for offering innovative library services to the users (Chan and Auster, 2005; Issa, 2021). Different emerging technologies were influencing information professionals to attend PD activities for enhancing relevant skills for the provision of satisfactory services to their customers (Cobblah and van der Walt, 2017); adoption of constant evolving changes was indispensable in the present era according to changing market requirements (Cossham and Fields, 2006).…”
Section: Data Analysis and Resultsmentioning
confidence: 99%
“…Extracted information showed that the factor of active leadership in librarianship played a positive role in motivating library professionals toward professional development-related activities on a practical basis. Different studies showed that leadership traits of librarians (Walter, 2006), problem-solving groups (Anyaegbu and Wali, 2020), Buddy system (Anyaegbu and Wali, 2020), coaching and mentorship (Anyim, 2021), teamwork (Issa, 2021), staff relations (Cobblah and van der Walt, 2017), good communication climates (Madukoma et al, 2014), and mentorship and peer coaching (Pan and Hovde, 2010). These different traits of dynamic library leadership played a significant part in the cognitive enhancement of library professionals to motivate them to develop required professional skills to serve the community through smart library devices.…”
Section: Data Analysis and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The digitization of library resources, development of library guides for library users to access digital resources. Wali, (2020); Anyim, 2021;Issa, 2021, andStephen et al (2021).…”
Section: Discussionmentioning
confidence: 99%
“…Changes in techniques of user services in universities influenced library professionals to take part in professional development activities enthusiastically (Stephen et al, 2021). Proper counseling of the library professionals influenced them towards capacity building and implementation of user centered services in the universities (Anyim, 2021 andIssa, 2021).…”
Section: Attitude Of Library Professionals Towards Professional Devel...mentioning
confidence: 99%